Teachers’ Challenges and Strategies in Teaching EFL in a Rural School (a Case Study at SMPN 5 Anggeraja) - Arnanda Cahyani Anton; Baso Jabu; Sultan Baa (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2025)
This study aims to determine the challenges faced by teachers in teaching EFL in rural school and the strategies used by teachers to overcome the challenges. The researcher conducted this study at SMPN 5 Anggeraja, located at Jl. Veteran No. 63, Cendana, Siambo village, Anggeraja District, Enrekang Regency. In this study, the researcher used a qualitative method. The data were collected through semi-structured interview (in-depth interview). The participants of this study were two English teachers at SMPN 5 Anggeraja. From results of the study showed that there are many challenges faced by teachers in teaching EFL at SMPN 5 Anggeraja: insufficient time, low of students concentration, students are confused when using English in the learning process, lack of vocabulary, how to deliver material, teachers ability, students interest in learning EFL, difficulty in translating, and inadequate facilities and infrastructure. In addition, the strategies used by teachers to overcome challenges in teaching EFL in rural school, are time management, conducting initial diagnostic test, providing games in the learning process, restitution to students, making interesting materials and giving exams, teachers’ self-reflection, providing motivational feedback, making the learning process fun, and cooperation with related parties for the procurement of Networks.